2004
DOI: 10.1097/01.pas.0000131544.18266.a4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Alpha-Methylacyl-Coenzyme A Racemase in Nephrogenic Adenoma

Abstract: Nephrogenic adenoma is a benign lesion composed of small glandular structures that develops along the urothelium with uncertain pathogenesis. Some investigators believe that nephrogenic adenoma develops by a metaplastic process in response to injury to the urothelium, while others believe that it arises from detached renal tubules. Nephrogenic adenoma may be present in the prostatic urethra and morphologically mimic prostatic adenocarcinoma. Alpha-methylacyl-coenzyme A racemase (AMACR), a recently identified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 25 publications
0
41
0
1
Order By: Relevance
“…Two common features found in nephrogenic adenomas but not in adenocarcinoma are (1) thick basement membranes and (2) granulation tissue-like background with prominent stromal edema and inflammatory cell infiltrate. 42 Large amount of mucin, mitoses, and necrosis are uncommon in nephrogenic adenomas. The diagnosis of nephrogenic adenoma should be primarily based on hematoxylin-eosin staining, because of its variable immunoprofile, which can be similar to that of adenocarcinoma.…”
Section: Nephrogenic Adenomamentioning
confidence: 99%
See 1 more Smart Citation
“…Two common features found in nephrogenic adenomas but not in adenocarcinoma are (1) thick basement membranes and (2) granulation tissue-like background with prominent stromal edema and inflammatory cell infiltrate. 42 Large amount of mucin, mitoses, and necrosis are uncommon in nephrogenic adenomas. The diagnosis of nephrogenic adenoma should be primarily based on hematoxylin-eosin staining, because of its variable immunoprofile, which can be similar to that of adenocarcinoma.…”
Section: Nephrogenic Adenomamentioning
confidence: 99%
“…42 There are many different patterns such as tubular (Figure 7, C), papillary, capillary, or signet ring-like. Most often the pattern is mixed.…”
Section: Nephrogenic Adenomamentioning
confidence: 99%
“…Positive immunohistochemical staining with AMACR and PAX-2 (markers of renal tubular epithelium) and absence of uroplakin immunostaining (present within normal urothelium) lend credence to this position. 23,24 Gross Appearance Nephrogenic adenoma may present grossly as an exophytic papillary or polypoid mass, mimicking carcinoma. Alternately, the lesion may appear flat.…”
Section: Nephrogenic Adenomamentioning
confidence: 99%
“…[4][5][6][7][8] Several studies have shown that PAX2 and PAX8 are expressed in nearly 100% of nephrogenic adenomas [9][10][11][12] and are helpful markers when the diagnosis of nephrogenic adenoma is difficult. In this study, we corroborated the frequent expression of PAX2 (93%) and PAX8 (100%) in our series of nephrogenic adenomas and identified a flat pattern associated with other traditional nephrogenic adenoma patterns that extended along the adjacent urothelium.…”
Section: Modern Pathology (2013) 26 792-798mentioning
confidence: 99%
“…2,3 By immunohistochemistry, nephrogenic adenomas are positive for the renal tubule markers cytokeratin 7 (CK7), CD10, alpha-methylacyl-coenzyme A racemase (AMACR), PAX2 and PAX8, but negative for bladder urothelium or prostate antigens. [4][5][6][7][8] The transcription factors PAX2 and PAX8 (paired box genes) are crucial proteins during the embryonic and fetal development of several organs, particularly intermediate mesoderm and Mü llerian-derived tissues, and are expressed in nearly 100% of nephrogenic adenomas in some series. [9][10][11][12] Tong et al 13 have shown that urothelial cells from the upper genitourinary tract are PAX8 positive, whereas urinary bladder urothelium lacks PAX8 expression.…”
mentioning
confidence: 99%